Properties of high-volume coal bottom ash in concrete production - Abdul Muiz, Hasim; Khairul Anuar, Shahid; Nur Farhayu, Ariffin; Nurul Natasha, Nasrudin; Muhamad Nor Syahrul, Zaimi (Elsevier Ltd, 2022)
Coal bottom ash (CBA) is a by-product of pulverized coal combustion that contributes to a large amount of industrial solid waste. Coal bottom ash has been frequently used in the manufacture of concrete as a partial substitute for cement and aggregate in recent years. Despite this, the enormous amount of coal bottom ash produced each day is disposed of in landfills without proper treatment. Thus, this study aimed to investigate the properties of the high amount of CBA in concrete manufacturing. CBA replaced in concrete as 50%, 60%, 70%, 80%, 90%, and 100% of fine and coarse aggregate replacement by using the volume replacement method. The tests carried out on concrete were fresh concrete workability and mechanical properties in terms of compressive strength, tensile strength, and flexural strength. After achieving all this strength, the correlation equations between each of the mechanical strengths were established. The results revealed that the high amount of CBA had the most influence on the slump reduction and weakest the flexural strength. Moreover, high volume usage of CBA material in concrete had achieved the targeted compressive strength at age 28 days of curing. The acceptable strength performance of concrete containing a high amount of CBA has potentially in the widespread use of this material in the construction industry.